Asparagus officinalis Exhibits Anti-Tumorigenic and Anti-Metastatic Effects in Ovarian Cancer - Xu, Guangxu; Kong, Weimin; Fang, Ziwei; Fan, Yali; Yin, Yajie; Sullivan, Stephanie A.; Tran, Arthur-Quan; Clark, Leslie H.; Sun, Wenchuan; Hao, Tianran; Zhao, Luyu; Zhou, Chunxiao; et al. (Frontiers in Oncology, 2021)
Ovarian cancer is one of the leading causes of female cancer death. Emerging evidence suggests that many dietary natural products have anti-tumorigenic activity, including that of asparagus officinalis. The current study aimed to assess the anti-tumorigenic and anti-metastatic effects of asparagus officinalis on serous ovarian cancer cell lines and a transgenic mouse model of high grade serous ovarian cancer. Asparagus officinalis decreased cellular viability, caused cell cycle G1 phase arrest and induced apoptosis in the OVCAR5 and SKOV3 cells. Induction of apoptosis and inhibition of cell proliferation was rescued by the pan-caspase inhibitor, Z-VAD-FMK, implying that its cytotoxic effects were mainly dependent on caspase pathways. Asparagus officinalis increased levels of ROS and decreased mitochondrial membrane potential with corresponding increases in PERK, Bip, Calnexin PDI and ATF4 in both cell lines. Treatment with asparagus officinalis also reduced ability of adhesion and invasion through epithelial–mesenchymal transition and reduction of VEGF expression. The combination of Asparagus officinalis with paclitaxel had synergistic anti-proliferative activity. Furthermore, Asparagus officinalis significantly inhibited tumor growth and reduced serum VEGF in a genetically engineered mouse model of ovarian cancer under obese and lean conditions, accompanied with a decrease in the expression of Ki67, VEGF and phosphorylated S6, and in an increase in phosphorylation of AMPK in the ovarian tumor tissues. Overall, our data provide a pr-clinical rationale for asparagus officinalis in the prevention and treatment of ovarian cancer as a novel natural product.